Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/jdv.17742
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo Treatment Impact score (VITs): development and validation of a vitiligo burden of treatment questionnaire using the ComPaRe Vitiligo e‐cohort

Abstract: Background Vitiligo management is challenging and requires long-term adherence of patients who often complain of the burden associated with treatment.Objective To develop and validate a patient reported measurement of the burden of treatment in vitiligo. MethodsThe study was nested within the ComPaRe Vitiligo e-cohort, an online e-cohort of vitiligo patients in France.Items were derived from a literature review and from the qualitative analysis of a survey using open-ended questions of 204 patients with Vitili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…4 The complexity of treatment regimens (including time taken to treat and experience satisfactory results) is expected to compound the burden experienced by patients and their caregivers. 155 Additionally, the likelihood of repigmentation is dependent on lesion location, with facial lesions being more responsive to treatment than lesions on the hands and feet. 156,157 It is also generally accepted that patient satisfaction is associated with nearcomplete (≥80%) repigmentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The complexity of treatment regimens (including time taken to treat and experience satisfactory results) is expected to compound the burden experienced by patients and their caregivers. 155 Additionally, the likelihood of repigmentation is dependent on lesion location, with facial lesions being more responsive to treatment than lesions on the hands and feet. 156,157 It is also generally accepted that patient satisfaction is associated with nearcomplete (≥80%) repigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Repigmentation of vitiligo lesions is typically a slow process, and psychosocial stress together with previous treatment failure can affect long‐term treatment adherence 4 . The complexity of treatment regimens (including time taken to treat and experience satisfactory results) is expected to compound the burden experienced by patients and their caregivers 155 . Additionally, the likelihood of repigmentation is dependent on lesion location, with facial lesions being more responsive to treatment than lesions on the hands and feet 156,157 .…”
Section: Discussionmentioning
confidence: 99%
“…Vitiligo is a common hypopigmentary dermatosis characterized by patches of depigmentation affecting approximately 0.1%–2.0% of the global population 1–5 . Although the disease does not directly cause physical impairment, it influences patients' quality of life and psychological health 6–8 …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Although the disease does not directly cause physical impairment, it influences patients' quality of life and psychological health. [6][7][8] Vitiligo treatment remains a challenge for dermatologists and is often unsatisfactory. Many options have been proposed and are currently available, including traditional pharmacological approaches such as topical and systemic corticosteroids, topical calcineurin phosphatase inhibitors, vitamin D derivatives, and phototherapy.…”
mentioning
confidence: 99%
“…Stacks of studies have shown that vitiligo is mostly a complex incorporation of abnormal immune responses, genetic predispositions, oxidative stress, metabolic alterations, and environmental factors [ 1 , 2 ]. The treatment modalities for vitiligo have mostly been nontargeted and generalized like oral or topical immunosuppressants, phototherapy, and surgical methods with limited efficacy and potential side effects [ 4 , 5 ]. There has been an emergence of innovative targeted therapies aimed at limiting disease progression and achieving repigmentation with a good safety profile based on a better understanding of the pathophysiology [ 6 ].…”
Section: Introductionmentioning
confidence: 99%